Assessment of Effects of Traditional Exercise on Galvanic Skin Response, Pulse Rate, and Blood Pressure in Prehypertensive Patients Attending Out-patient Department Clinic of Janaki Medical College, Nepal: Assessment of Effects of Traditional Exercise on Galvanic Skin Response, Pulse Rate, and Blood Pressure in Prehypertensive Patients Attending Out-patient Department Clinic of Janaki Medical College, Nepal - Das, Dr. Rajesh Chandra (International Journal of Pharmaceutical & Biological Archive, 2020)
Psychological stress, in this era of urbanization, has become a part and parcel of our lives, has led to a serious problem affecting different life situations and carries a wide range of health-related disorders, and has to observe the effects of traditional exercise pranayama on galvanic skin response (GSR), pulse rate, and blood pressure (BP). This was an open-labeled, prospective, uncontrolled, single-centered, single-arm, comparative, and clinical intervention study conducted in the Department of Medicine, Janaki Medical College, for 2 months period January–February 2018 on 15 prehypertensive subjects. Of which 10 were male and 5 were females, all in the age group of 22–35 years with a body mass index of 19.63–30.11 with an average of 24.80. No significant change was seen when baseline GSR reading was compared with 15th-day reading, but on 30th day significant change observed. When the baseline value of pulse was compared with that of the 15th and 30th days, a good positive change was seen in resting pulse. Similarly, BP recording also showed a good positive effect when baseline value was compared with that 15th and 30th days. The study concludes that practicing Pranayama on a regular basis increases the parasympathetic tone and blunts the sympathetic tone of the body. This has shown good beneficial effects on pulse, BP, and GSR.